2007
DOI: 10.1080/87559120701225037
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Porcine Fat Quality in Meat Technology: A Review

Abstract: Pork is the most important meat product globally. The aim of this review was to assess whether fat quality of pork is important in meat processing. Good quality backfat can be defined as firm and white. Problems associated with the use of poor fat quality (soft fat) in meat products were found to be insufficient drying, oily appearance, rancidity development, seperation between muscle, and adipose tissue on cutting. Criteria were set for good quality fat, in terms of physical properties and fatty acid composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 99 publications
1
52
0
3
Order By: Relevance
“…Fatty acid (FA) composition is an important aspect of meat quality because it influences technological aspects of meat quality (Hugo & Roodt, 2007) and has implications on human health. While polyunsaturated fatty acids (PUFAs) generally have more health benefits than saturated fatty acids (SFAs), emphasis must be placed on the type of PUFAs consumed, specifically the balance between C18:3n (n-3) and C18:2n (n-6) because the ratio of n-6 : n-3 is a risk factor for cancers, coronary heart disease and the formation of blood clots, which could lead to a heart attack (Enser, 2001;Wood et al, 2003;Walker et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Fatty acid (FA) composition is an important aspect of meat quality because it influences technological aspects of meat quality (Hugo & Roodt, 2007) and has implications on human health. While polyunsaturated fatty acids (PUFAs) generally have more health benefits than saturated fatty acids (SFAs), emphasis must be placed on the type of PUFAs consumed, specifically the balance between C18:3n (n-3) and C18:2n (n-6) because the ratio of n-6 : n-3 is a risk factor for cancers, coronary heart disease and the formation of blood clots, which could lead to a heart attack (Enser, 2001;Wood et al, 2003;Walker et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the SFA/PUFA ratio was higher and the iodine value tended to be lower for the subcutaneous fat of the pigs fed the Cometa diet than for the subcutaneous fat of the pigs fed the Alamo diet. However, the subcutaneous fat of fresh thighs obtained from the pigs fed both Cometa and Alamo diet had iodine value and C 18:2n-6 fatty acid percentage within the limits (70% and 15%, respectively) fixed by the production protocols of the Parma and San Daniele hams (Consorzio del Prosciutto di Parma 2015; Consorzio del Prosciutto di San Daniele 2015), and a SFA percentage higher than the minimum value of 41% reported for acceptable fat firmness (Hugo and Roodt 2007). Moreover, no appreciable differences were observed in the color of subcutaneous fat and biceps femoris from pigs fed the Cometa and Alamo diets.…”
Section: Discussionmentioning
confidence: 77%
“…(P≥0.05). Hugo and Roodt (2007) reported that fat gives meat products some of their textural attributes such as hardness, gumminess, juiciness and chewiness, as a result of its physical characteristics that depend on the fat's temperature and fatty acid composition. Generally, the firmness increases with more saturated fat (Ospina et al, 2011).…”
Section: Resultsmentioning
confidence: 99%